2010
DOI: 10.1007/s00464-010-1132-9
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic inguinal herniorrhaphy in babies weighing 5 kg or less

Abstract: Laparoscopic inguinal hernia repair for babies weighing 5 kg or less is feasible, safe, and perhaps even less technically demanding than open herniotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…10 There have been concerns regarding the higher rates of recurrence in laparoscopic surgery (4%) compared with 2% in open surgery, 3 and the articles referenced had patients ranging from 3 months to 18 years. 10,11 Recent articles studying patients under the age of 1 year 4 and babies weighing 5 kg or less 6 have suggested that the recurrence rate may be lower in the subset of patients undergoing laparoscopic surgery under the age of 1 year than those quoted for open procedures. Their reasoning for this is related to the thin sac that needs to be dissected in open surgery and the advantage of a magnified field of view during laparoscopic surgery so that sutures can be positioned precisely.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…10 There have been concerns regarding the higher rates of recurrence in laparoscopic surgery (4%) compared with 2% in open surgery, 3 and the articles referenced had patients ranging from 3 months to 18 years. 10,11 Recent articles studying patients under the age of 1 year 4 and babies weighing 5 kg or less 6 have suggested that the recurrence rate may be lower in the subset of patients undergoing laparoscopic surgery under the age of 1 year than those quoted for open procedures. Their reasoning for this is related to the thin sac that needs to be dissected in open surgery and the advantage of a magnified field of view during laparoscopic surgery so that sutures can be positioned precisely.…”
Section: Discussionmentioning
confidence: 98%
“…However, Turial et al, 6 dealing with babies weighing under 5 kg, found that 4.1% of post-laparoscopic hernia repair required orchidopexy. Our series had a lower rate of 2.4% iatrogenic cryptorchidism, but our mean weight at time of surgery was 5.3 kg, which is higher than the mean weight of 3.9 kg in the cases of Turial et al 6 They calculated a 65.5% increase in risk for secondary high testis for each 1 kg less in weight.…”
Section: Testicular Ascentmentioning
confidence: 97%
See 2 more Smart Citations
“…Turial et al . reported a 4% incidence of testicular ascent after laparoscopic inguinal herniotomy in babies weighing 5 kg or less 34 . Schier reported a 0.2% incidence of testicular atrophy just 4 weeks after laparoscopic herniotomy 35 .…”
Section: Discussionmentioning
confidence: 99%